(untitled) (Research, Society and Development, 2023)
Introduction: Renal failure is characterized as a decline in kidney function. This disease can be classified, according to its evolution, into Acute Renal Failure (ARF), when there is sudden but reversible loss, or Chronic Renal Failure (CRF), when there is progressive loss. It is an important cause of mortality and hospitalizations and generates significant costs for the healthcare system. The objective of this work is to analyze hospitalizations and the epidemiological profile of renal failure in Brazil between 2012 and 2022. Methodology: This is an epidemiological study carried out from 2012 to 2022 based on data from the SUS health information department (Health Unic System). The variables used were: hospital admissions, deaths, age group, color/race, sex, hospital expenses and health macro-region. Results: A total of 1185600 hospitalizations were obtained, of which 151053 resulted in death. The most affected portions of the Brazilian population were: men (56.9%); white race (35.2%); ages between 59-69 years (41.3%). Furthermore, it was demonstrated that the region most affected, both in terms of number of hospitalizations and deaths and hospital expenses, was the Southeast. Conclusion: Kidney failure is a highly relevant disease that causes physical, social and emotional damage. In this sense, it is important to carry out preventive actions in relation to this condition, since its main etiologies are related to modifiable circumstances.